Cardiac complications of systemic drugs used in dermatology - Palaniswami, Saranya; Saminathan, Praveen Vasanthi; Ramasamy, Sri Vaishnavi (International Journal of Research in Dermatology, 2024)
Within the realm of dermatology, the use of systemic drugs carries implications beyond skin health, often intersecting with cardiovascular outcomes. From antihistamines to biologics, medications prescribed for dermatological conditions may pose varying degrees of risk to the heart. Understanding these potential cardiac side effects is paramount in the comprehensive management of dermatologic patients. This journal article delves into the intricate relationship between systemic dermatologic drugs and cardiovascular health, elucidating the mechanisms underlying cardiotoxicity, identifying patient-specific risk factors, and offering insights into optimizing therapeutic regimens while safeguarding cardiac well-being. Through this exploration, we aim to equip dermatologists with the knowledge necessary for delivering safe and effective care, ensuring the holistic health of their patients.